Cordocentesis in multifetal pregnancies - Fuanglada Tongprasert (2018)
Objective: To describe the experiences in diagnostic cordocentesis in twin pregnancies at midpregnancy Methods: The database and medical records of pregnant women attending Maternal Fetal Medicine Unit of the hospital for diagnostic cordocentesis at midpregnancy between January 1989 and September 2006 were retrospectively reviewed. Results: During 17 years of experience, 4241 cordocenteses at midpregnancy were performed for prenatal diagnosis, including 59 procedures in 30 multiple pregnancies (29 twins and 1 triplet). The mean gestational age at the time of cordocentesis was 19.5 ± 1.6 weeks. Success rate of the samplings was 98.3% with one sample was maternal blood contamination. Averaged-time used of the procedures was 8.2 minutes (range 1-45 minutes). The procedure-related complications included transient bleeding at puncture site (8.5%) and transient fetal bradycardia (22.0%). The total fetal loss rate was 10.5% but there was no cordocentesis-related fetal loss (0.0%), defined as a fetal loss within 2 weeks after the procedure. Conclusion: This study may provide a new insight on the safety of cordocentesis in multifetal pregnancies at midpregnancy. The procedure-related fetal loss is not as high as reported in the past. This study suggests cordocentesis be a relatively safe and highly successful in obtaining fetal blood samples. Copyright © 2007 John Wiley & Sons, Ltd.